Marine electrical equipment and practice - McGeorge, H. D. (Marine engineering series., 1993)
Caters for marine engineer candidates for Department of Transport Certification as Marine Engineer Class One and Class Two. It covers the various items of ships' electrical equipment and explains operating principles.